2010
DOI: 10.1016/j.otohns.2009.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Are cell salvage and autologous blood transfusion safe in endonasal surgery?

Abstract: Cell saver blood is widely accepted in surgery. It offers many advantages in elective operations in which blood loss is expected to be significant. Cell saver blood has been transfused from contaminated fields in other forms of surgery without an associated increase in morbidity. There is good evidence that antibiotic prophylaxis is mandatory in this setting. There is no direct evidence that cell salvage blood is safe in endonasal surgery. Cell salvage is part of a multimodality approach, including the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…Interestingly, cell saver was used in a few patients in both groups, despite the inclusion of contaminated respiratory tract mucosa in the surgical field. The use of cell saver in fields where there is potential microbiologic contamination has been questioned . Acute preoperative normovolemic hemodilution and the use of erythropoietin were rarely used, while transfusion protocols were more often but not uniformly applied in this patient population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, cell saver was used in a few patients in both groups, despite the inclusion of contaminated respiratory tract mucosa in the surgical field. The use of cell saver in fields where there is potential microbiologic contamination has been questioned . Acute preoperative normovolemic hemodilution and the use of erythropoietin were rarely used, while transfusion protocols were more often but not uniformly applied in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…The use of cell saver in fields where there is potential microbiologic contamination has been questioned. 29,30 Acute preoperative normovolemic hemodilution and the use of erythropoietin were rarely used, while transfusion protocols were more often but not uniformly applied in this patient population. Given the evidence of safety and efficacy of reducing perioperative transfusion using restrictive transfusion practices, broader application of this approach represents a sensible improvement intervention in this population.…”
Section: Intraoperative Management and Patient Blood Managementmentioning
confidence: 99%
“…However, its use for endonasal surgeries is controversial because the site of surgery and blood collection can be contaminated by the nasal flora. 29 Use of an intratumoural injection of fibrin glue has been described in a few case reports. 26 In comparison to the study by Ezri et al, 25 in which the open surgical technique was used, and the mean loss was 4 800 ± 1 600 ml, the patients in this study experienced a median blood loss of 500 ml, but endoscopic surgical resection was used these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Although few data exist that could prove the lower morbidity of transnasal approaches to the skull base in comparison to the external access, Shane and Panizza summarized important facts in their review. 17 Based on two investigations, 18,19 they concluded that endoscopic transnasal approaches reduce the amount of blood loss significantly. In addition, facing the growing skull and the midface, in particular, every effort has to be considered not to influence the natural growth negatively.…”
Section: Discussionmentioning
confidence: 99%